Increasing Online Information Retention: Analyzing the Effects - Eric Zeglen; Joseph A. Rosendale (Flexible Learning Association of New Zealand, 2018)
While online education offerings continue to grow in the higher education marketplace, issues of student achievement and course rigor remain challenges to the underlying instructional model and alignment with institutional missions. Pedagogically, instructors and course designers can mitigate these issues by leveraging technology to further enhance students' cognition and knowledge retention within the online domain. This study analyzed the effects of visual hints and elaborate feedback embedded in serious educational games to determine the effects on student learning and information recollection. Using a quasi-experimental design and quantitative testing methods, significant differences were found among 3 groups of students within an online educational environment based on differing forms of feedback within the game.  Supporting information processing theory, mean scores on comprehension tests indicated that participants exposed to elaborate feedback and visual hints performed better than control groups in an online learning environment.